A new preparation method of Fe2B: Generating rodlike/scale-like Fe2B by dealloying Fe78Si9B13 atomized particle. (March 2018) - Liu, Shuai; Bian, Xiufang; Liu, Jie; Wang, Junzhang; Yu, Mengchun; Yang, Yinghui; Fan, Runhua
Abstract: Chemical dealloying is currently studied to produce nanoporous structure suited for use in battery, catalysis, sensors and other electrochemical applications. Moreover, experimental values on mechanical properties or stability of the Fe2 B are limited since it is very difficult to extract Fe2 B from bulk casting irons or to investigate an effective method to prepare Fe2 B sample. Here, we have prepared rodlike/scale-like Fe2 B by dealloying Fe78 Si9 B13 atomized particle during which the Fe and FeSi phases are etched away, leaving Fe2 B phase. The morphology of Fe2 B can be controlled from rod-like to scale-like, amplifying the applied fields of iron borides on the surface of parts and components. The magnetic property (saturation magnetization, remanence and coercivity) evolution of Fe78 Si9 B13 during chemical dealloying is also investigated. Graphical abstract: We found a new preparation method of Fe2 B, generating rodlike/scale-like Fe2 B by dealloying Fe78 Si9 B13 atomized particle during which the Fe and Fe-Si phases are etched away, leaving Fe2 B phase. The morphology of Fe2 B can be controlled from rod-like to scale-like, amplifying the applied fields of iron borides on the surface of parts and components. Highlights: For the first time, Fe2 B is prepared by chemical dealloying Fe78 Si9 B13 atomized particle. The morphology of Fe2 B can be controlled from rod-like to scale-like. The magnetic property evolution of Fe78 Si9 B13 during chemical dealloying is investigated.